Perineal Ectopic Testis in One and A Half Year Old Child As A Rare Congenital Anomaly: A Case Report: Ektopik Testis Perineal pada Anak Satu Setengah Tahun Sebagai Kasus Kelainan Kongenital Yang Langka: Laporan Kasus - Surya, Prima Ardiansah; Faadilah, Ashifa Hasna; Sriyono (Medicra (Journal of Medical Laboratory Science/Technology), 2023)
Ectopic testis is described as an abnormality of testicle development in which one or both testicles aren’t descending through the testicle normal pathways. Among all newborns with undescended testis, only 1% are diagnosed as ectopic testis. In this case, an 18 months old boy was presented to hospital with chief complaint of impalpable testis dextra. Phsical examination showed the right testis was not palpable in the scrotum and perineum. Ultrasonography examination showed a right testis in the perineum with normal volume and vascularization. Right orchidopexy was performed to correct the location of the testis. Early diagnostic of ectopic testis must be done through anamnesis, physical examination, and advanced examination. Limited faciliiesy and lack of parental knowledge make the patients come late to health facility. The conclusion of this study is knowledge among parents and skills of health workers concerning congenital anomaly especially undescensus testis should be improved.